"What Exactly Is a Black?": Interrogating the Reality of Race in Jean Genet's The Blacks - Debby Thompson (Studies in 20th & 21st Century Literature, 2002)
On the dedication page of The Blacks, Genet writes "One evening an actor asked me to write a play for an all-black cast. But what exactly is a black? First of all, what's his color?" Prefiguring major issues and paradoxes of African American cultural studies today, The Blacks insists on the very real ways in which the black/white racial binary, like the very concept of race itself, is lived and socially enforced, and at the same time argues that the binary is ultimately a fiction, made real through performative reification. Genet's "clown show," ambiguously reversing the blackface minstrelsy tradition, dramatizes how racial identity can become internalized and naturalized through cultural myths of interracial rape and colonialist narratives of a "heart of darkness," an imaginary site from which "black essence" arises. These racist performance traditions and narratives are so powerful and resilient that attempts to protest them become subtle and unwitting ways of re-creating them. The Blacks' parody of the minstrel tradition to interrogate all racial identity is so permanently suspended in a dialectic of both reinforcing the black/white binary and invalidating it, that the play's strategies present vital paradigms for the study of other and diverse interrogations of racial ontologies.
Keywords: The Blacks; Jean Genet; all-black cast; what is black; African American cultural studies; black/white; socially enforced; racial binary; race; performative; fiction; clown show; blackface; racial identity; internalized; naturalized; culture; cultural myths; interracial rape; colonialist narratives; racist performance traditions; racial ontologies